Evaluasi Penggunaan Aplikasi Sehat IndonesiaKu (ASIK) - Selfi Rahayu; Suci Artanti; C. Ermayani Putriyanti (STIKES Ngesti Waluyo, 2025)
Digitalization of health services, particularly through the Sehat IndonesiaKu Application (ASIK), is expected to enhance the efficiency and effectiveness of patient data recording in community health centers. The use of ASIK in the field still faces several challenges, including staff adaptation, limited technological infrastructure, and training needs. Evaluating the use of ASIK is crucial for identifying the application's strengths and weaknesses and formulating improvement recommendations. This study aims to evaluate the use of ASIK by health workers in community health centers of Temanggung Regency. The research uses quantitative methods, a non-experimental approach, and a descriptive design. The study population consisted of 70 health workers using ASIK at two community health centers in Temanggung Regency, with a total sampling applied. Data were collected through questionnaires and analyzed using univariate descriptive analysis and the Independent Samples Test. The results showed that healthcare workers were neutral regarding the advantages of ASIK in terms of time, data, and integration, but agreed on the aspects of devices and place. Health workers were neutral on technical, user, and data aspects, and there was no significant difference in ASIK usage between the two types of Community Health Centers (p-value> α). The conclusion of this study is that the use of ASIK still faces several obstacles, including time constraints, concurrent manual and digital recording, government-subsidized internet data packages, a shortage of data entry officers, and data accuracy issues. The government and Community Health Centers are advised to improve infrastructure, training, and coordination to optimize ASIK. ASIK users should also improve their skills and commitment in using ASIK to enhance the efficiency and effectiveness of patient data recording at Community Health Centers.